Relationship between Use and Purpose of Performance Measurement Indicators: the case of electrification cooperatives in Brazil. - Munaretto, Lorimar Francisco; Luiz Corrêa, Hamilton (Revista de Administração da UFSM, 2017)
The purpose of this study was to verify the relationship between the use and the purposes of the indicators of performance measurement in Cooperatives of Electrification (CEs). It is a quantitative research of a correlational nature, with data obtained in the months of February, March, 2013, with the CEs of Brazil. The results obtained demonstrate the confirmation of all the hypotheses raised, with a strong correlation between the use of the indicators for strategic decision making (0.635) and monitoring and control (0.632) and moderate correlation with education and learning purposes (0.548) , Legitimacy (0.507) and external communication (0.476).